Periostitis ossificans (Garrè's osteomyelitis): An unusual case - Deepesh Singh; Priya Subramaniam; Panduranga Deepak Bhayya (Wolters Kluwer Medknow Publications, 2015)
Garrè's sclerosing osteomyelitis is a specific type of chronic osteomyelitis that mainly affects children and young adults and is commonly associated with odontogenic infection. The paper describes an unusual case of Garrè's osteomyelitis in an 11-year-old boy, in whom the condition arose following poor oral hygiene and periodontal problems in relation to permanent mandibular left first molar. Clinically the patient presented with bony hard, nontender swelling and the occlusal radiograph revealed pathognomic feature of "onion skin" appearance.